Bilateral Adrenal Metastases in Non-small Cell Lung Cancer Patient at Baseline 18F-FDG PET-CT Scan– A Rare Case Report - Kar, Rashmi; Mutsuddy, Pupree; Mandal, Tapati; Nath, Khokon Kumar; Siddique, Abu Bakker; Begum, Shamim MF (Bangladesh Journal of Nuclear Medicine, 2022)
Bilateral adrenal metastases at the time of initial diagnosis of non-small cell lung cancer is a rare phenomenon. In elderly patients with an extra-adrenal malignancy and other nodal metastases, it is difficult to diagnose the etiology of adrenal mass by invasive procedure. Fluorine-18 FDG PET-CT scan can be an effective alternative in this type of patient to characterize adrenal masses as metastatic using several metabolic and imaging parameters in a single setting. Here we present a rare case of synchronus bilateral adrenal metastatic masses found in an elderly gentleman with non-small cell lung cancer (NSCLC) diagnosed during his baseline evaluation by 18F- FDG PET-CT scan. Bangladesh J. Nuclear Med. 24(1&2): 51-56, 2021